42.1k views
5 votes
Pleaseeeee helppppppp Simplify [3^-2]^4

User Yashwanth
by
5.1k points

1 Answer

1 vote

Answer:


(1)/(6561)

Explanation:

This is a "power" raised to another "power" problem. Lets see the rule of exponents that dictates solving this type of problem.

Power rule of Exponents:


(a^b)^c=a^(bc)

We basically multiply the powers together. So this problem becomes:


[3^(-2)]^4=3^(-2*4)=3^(-8)

We can use another property to make it simpler. The property is:


a^(-b)=(1)/(a^b)

So, the problem becomes:


(1)/(3^8)=(1)/(6561)

In fractional form, this is the answer:
(1)/(6561)

User Manduro
by
4.7k points